Komentář k nejdůležitějším a nejnovějším studiím s inhibitory PCSK9 - Češka, Richard (Vnitrni lekarstvi, 2019)
The paper provides a brief overview of the key studies focused on PCSK9 inhibitors. It mainly examines positive results of the FOURIER studies on evolocumab, the SPIRE study on boccocizumab and the ODYSSEY Outcomes study on alirocumab. All these studies have not only shown a significant decrease in LDL-cholesterol levels, but also the reduction of cardiovascular events just correlating with these levels. The treatment leading to a dramatic drop in LDL-cholesterol levels was safe and well tolerated by patients. All the studies provided with comments demonstrate a positive impact of biological treatment of hypercholesterolemia on cardiovascular disease and confirm validity of the hypothesis saying “the lower the better”, at least for LDL-cholesterol. In conclusion, Professor Braunwalds hypothesis is mentioned saying that this treatment might eventually lead to as much as eradication of atherothrombotic cardiovascular diseases. Key words: alirocumab - bococizumab - evolocumab - FOURIER - cardiovascular disease - LDL-cholesterol - ODYSSEY Outcomes - SPIRE.
Keywords: alirocumab - bococizumab - evolocumab - FOURIER - cardiovascular disease - LDL-cholesterol - ODYSSEY Outcomes - SPIRE; Cholesterol, LDL; monoklonální protilátky; Cardiovascular Diseases; proproteinkonvertasa subtilisin/kexin typu 9; PCSK9 Inhibitors; PCSK9 inhibitory; Proprotein Convertase 9; LDL-cholesterol; Anticholesteremic Agents; anticholesteremika; Antibodies, Monoclonal; Humans; Hypercholesterolemia; hypercholesterolemie; kardiovaskulární nemoci; lidé